Stakeholder preferences for supervised consumption site design, staff, and ancillary services: A scoping review of feasibility studies. (1st January 2022) - Kryszajtys, David T.; Xavier, Jessica; Rudzinski, Katherine; Guta, Adrian; Chan Carusone, Soo; Strike, Carol J.
Abstract: Background: Supervised consumption services (SCS) prevent drug related harms for people who use drugs (PWUD) and often require a feasibility study before implementation. While there is a growing feasibility study literature, it has not been synthesized for use by researchers and SCS planners. We conducted a scoping review of feasibility studies reporting on preferred SCS design characteristics, staffing models and ancillary services. Materials and methods: We searched academic databases and grey literature sources with key terms related to SCS and feasibility studies. Team members reviewed search results and included feasibility studies with findings relevant to SCS design, staff, or ancillary services. The research methods and findings from included studies regarding design elements were charted, collated, and reported. Results: The search yielded 1347 results; 26 met eligibility criteria for review. Most reported preferences for SCS location, hours and wait times. Few reported preferences for security, space allocation by type of drug use, and onsite opioid prescribing. PWUD generally preferred aligning design elements with the goal of harm reduction for clients while other stakeholders valued treatment as a goal. Specific considerations varied by implementation context. Conclusions: These results can be used by SCS planners and researchers to help resolve implementation concerns and improve uptake among PWUD, which is critical during an overdose crisis. Future feasibility studies should ask about design preferences that may be significant to uptake but are not commonly covered in studies. These should also explore how context influences preferences to develop an evidence-based framework for context-specific design decisions. Highlights: We reviewed SCS design, staff, and service preferences in 26 feasibility studies. Most studies reported preferences for SCS location, hours and wait times. Few studies described design preferences by method of drug consumption. Preferences of people who use drugs aligned with harm reduction goals. Some stakeholders wanted SCS to promote substance use treatment services.